Vanilla montana Ridl.: A NEW LOCALITY RECORD IN PENINSULAR MALAYSIA AND ITS AMENDED DESCRIPTION - Mohd Akmal, Mohd Raffi; Farah Alia, Nordin; Jamilah, Mohd Salim; Hardy, Adrian A. Chin (Penerbit UMT, 2020)
Among the seven Vanilla species native to Peninsular Malaysia, Vanilla montana was the first species to be described. But due to its rarity, it took more than 100 years for the species to be rediscovered in two other localities. This paper describes the first record of V. montana in Negeri Sembilan with preliminary notes on its floral development and some highlights on the ecological influences. We also proposed a conservation status for the species. The data obtained will serve as an important botanical profile of the species, and it will add to our knowledge gaps on the distribution of this distinctive orchid in Malaysia.